Handbook of Environmental Materials Management - Hussain, Chaudhery Mustansar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This reference work analyzes and assesses global environmental management techniques for environmental materials with a focus on their performance and economic benefits, proposing eco-friendly solutions and designating policies that will sustain the environment for future generations. It addresses management of environmental materials as not only a complex anthropogenic problem, but also as an expensive problem that needs to be managed sustainably. Simultaneously, it considers the environmental and economic benefits involved in the high levels of investment and operation costs required to develop effective materials collection and management systems in modern society. .
Introduction -- Modern inventive perspective of environmental materials management -- Major Environmental Issue and problems -- Environmental Site Remediation -- Hazardous Waste Management -- Management of Radioactive Wastes Section V: Management of Special Waste: CO2, CH4 , NOx, SO2, Carbon Particles and Oil Spills -- Environmental Analysis -- Environmental Treatment Technologies -- Environmental Management of Biomaterials -- Environmental Modeling (Mathematical Modeling and Environmental Problems) -- Environmental Nanotechnology: Management of Nano-Waste or Nanomaterials -- Fate and Transport of Pollutants: LCA -- Environmental Risk Assessment -- Environmental Policy, Laws and Economics -- Pollution Prevention, Sustainability, and a Green World -- The Future of Modern Environmental Materials Management. .
Keywords: Materials -- Analysis; Environmental management; Environmental economics; Environmental engineering; Biotechnology; Bioremediation; Nanotechnology; Biomaterials; Characterization and Analytical Technique; Environmental Management; Environmental Economics; Environmental Engineering/Biotechnology.; Nanotechnology; Biomaterials